2008
DOI: 10.1038/ijo.2008.13
|View full text |Cite
|
Sign up to set email alerts
|

Effects of leptin on energy metabolism in β-less mice

Abstract: Objective: To investigate the impact of b-adrenoceptor deficiency on the metabolic effects of leptin. Measurements: Leptin was infused subcutaneously through an osmotic minipump in wild-type (WT) and b 1 /b 2 /b 3 -adrenoceptor knockout (b-less) mice and its effects on food intake, energy expenditure, carbohydrate and lipid utilization as well as on the levels of expression of the brown adipose tissue (BAT), thermogenic marker uncoupling protein-1 (UCP1) and type II deiodinase (D2) mRNAs were compared. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…It is consistent with the thermogenic effect of leptin on days 2–6 being reduced by about 50% in mice that lack all three β-adrenoceptors (see section Acute Stimulation of Energy Expenditure). However, the same paper reports that leptin did not cause weight loss over 6 days in either wild type or “β-less” mice other than by reducing food intake (Asensio et al, 2008). …”
Section: Detection Of Non-acute Thermogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…It is consistent with the thermogenic effect of leptin on days 2–6 being reduced by about 50% in mice that lack all three β-adrenoceptors (see section Acute Stimulation of Energy Expenditure). However, the same paper reports that leptin did not cause weight loss over 6 days in either wild type or “β-less” mice other than by reducing food intake (Asensio et al, 2008). …”
Section: Detection Of Non-acute Thermogenesismentioning
confidence: 99%
“…In rats, intracerebroventricular injection of leptin increased body temperature after an hour; peripheral administration took 3 h (Luheshi et al, 1999). Subcutaneous administration has been shown to increase energy expenditure within 12 h in suckling rats (Stehling et al, 1996) and 2 days when infused by minipump in normal mice (Asensio et al, 2008). Leptin increases noradrenaline turnover in brown and white adipose tissue (Collins et al, 1996b) and electrical activity in sympathetic nerves (Dunbar et al, 1997; Hausberg et al, 2002).…”
Section: Acute Stimulation Of Energy Expenditurementioning
confidence: 99%
See 1 more Smart Citation
“…Leptin treatment was found to increase energy expenditure (oxygen consumption),as well as increased thermogenic marker uncoupling protein-1 and type II deiodinase mRNA levels 1.7-and 3-fold,respectively,in mice [256]. Table 11: Serum proinflammatory cytokines and leptin concentrations in obese children at prepubertal age compared with healthy children of the same age (according to Aygun et al [253] and Kapiotis et al [254]; with own modification).…”
Section: T Gondii Infectionmentioning
confidence: 99%
“…Multiple cytokines and acute inflammation that raise leptin levels may have a potential role also in inflammatory anorexia [641] , especially that leptin treatment increased energy expenditure (oxygen consumption) in animals [656] . It should be noted that in mice with T. gondii infection the dual anorexia and hypermetabolic states were associated with the elevation of TNF-α, IL-1β, IL-2, IL4, IL-5, IL-6, IL-10, and IFN-γ levels [657,658] , and it was reported that various cachectic-anorexic conditions resulted from interactions among cytokines and neurotransmitters as mediators of neurologic and neuropsychiatric manifestations of disease [659,660] .…”
Section: T Gondii Infectionmentioning
confidence: 99%